Catalytic anode and method for electrolytic chlorine production

By using conductive metallurgical layers formed by metal oxide compounds of ruthenium, tin and titanium in electrolytic chlorine production systems, the problems of high cost and poor durability of catalytic anode are solved, efficient electrolytic operation and extended anode life are achieved, and the cost and By-product generation.

CN119162612APending Publication Date: 2024-12-20INFINEUM INT LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410792003.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-20
Filing Date
2024-06-19
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The catalytic anode in the existing electrolytic chlorine production system is expensive and has poor durability, which is prone to loss of efficiency due to acid etching and competitive oxygen evolution reactions, and the commonly used precious metal catalysts increase manufacturing complexity.

Method used

Using a conductive metallurgy layer, metal oxide compounds containing ruthenium, tin and titanium, a metallurgy layer with agglomerated particles mixed with voids is formed through specific process conditions and composition ratios, thereby improving the catalytic activity, selectivity and mechanical adhesion of the anode. , reduce the overpotential.

Benefits of technology

It realizes efficient electrolytic operation, extends the anode life, reduces costs, improves the selectivity and acid corrosion resistance of chlorine-eliminated reactions, and reduces the generation of unnecessary electrolytic by-products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162612A_ABST
    Figure CN119162612A_ABST
Patent Text Reader

Abstract

The invention relates to a method for producing a catalytic anode for an electrolytic chlorine production system which produces chlorine gas from an aqueous solution by means of a chlorine evolution reaction. These anodes include an electrically conductive metallurgical layer substantially comprising ruthenium, tin, and titanium. The desired characteristics of such a metallurgical layer can be achieved by a production process employing specific control of reactants and process conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalytic anode for an electrolytic chlorine production system, wherein chlorine gas is generated from an aqueous solution containing chloride ions by a chlorine evolution reaction. Such chlorine production systems are particularly useful for industrial treatment and purification of wastewater, such as ballast water treatment systems and industrial and municipal water. They can also be used in particular for the industrial production of chlorine gas in a chlor-alkali process. Background Art

[0002] The chlorine evolution reaction ("CER") is a well-known reaction in industrial chemistry that can be used both for large-scale production of chlorine for collection and for the generation of chlorine gas for immediate use. The chlor-alkali process generates chlorine gas and sodium hydroxide by electrolysis of an aqueous sodium chloride solution; the products are recovered and put into subsequent industrial use. Chlorine gas is also an effective biocide, so electrochlorination systems are also used independently for water purification based on the in-situ generation of chlorinated water and its biocidal effect. Microbially contaminated water can be effectively treated by electrochlorination, which is deployed in various situations such as industrial wastewater and general water sanitation. In addition, ships increasingly carry onboard ballast water treatment systems to treat water in ballast tanks before discharge. Ships sailing long distances are likely to introduce alien aquatic organisms into local ecosystems by discharging ballast water obtained at a distance. Invasive alien species can have a considerable impact on the balance of local ecosystems. Electrochlorination systems driven by generators on board provide an effective and immediate solution for treating such water before discharge.

[0003] The effective industrial application of electrolytic chlorine production systems and methods depends on electrolytic cells that can operate efficiently for a long time. In order to promote the generation of chlorine at the anode, it is common in the art to configure a catalytic coating on the surface of the anode facing the electrolyte to catalyze the chlorine evolution reaction. Such a catalytic coating usually contains a significant amount of one or more precious metals, of which iridium and ruthenium are the most commonly used, thereby significantly increasing the cost and complexity of anode manufacturing. There is still a continuous need in the art for a novel catalytic anode that can more cost-effectively meet various technical considerations related to industrial or municipal electrolytic chlorine production environments.

[0004] When selecting a catalytic coating for an electrochlorination anode, various technical considerations must be taken into account.

[0005] First, the selected catalyst must be sufficiently selective for the chlorine evolution reaction to reduce the efficiency loss caused by the competitive oxygen evolution reaction that may otherwise be caused by the electrolytic separation of water in the aqueous solution at the anode. Secondly, the catalytic coating must be durable enough to withstand long-term operation and the acidification of the electrolyte that may occur with electrolytic chlorine production. Durability also requires good mechanical adhesion of the catalyst to the surface of the anode substrate. Third, the anode coating should have high conductivity to improve electrical efficiency by avoiding the need for large overpotentials to drive the electrolyzer. In practice, due to efficiency losses, a certain degree of overpotential is usually apparent in the electrolyzer; however, a lower degree of overpotential provides an important relative efficiency gain, and maintaining a lower overpotential during long-term operation provides another relevant measure of electrode durability and effective life.

[0006] The physical durability of the catalytic coating on the anode can be assessed by its performance in long-term tests and by examination of its morphology, most suitably by scanning electron microscopy. In fact, catalytic anode coatings in the art typically exhibit an outer surface morphology similar to that of a dry lake bed, with Figure 1 The appearance of finely-deposited sediments widely interrupted by characteristic "mud cracks" is shown in Figure 1. These cracks provide weak points in the catalyst layer and allow electrolyte and reactive species to penetrate downward toward the anode substrate, resulting in a degradation process that weakens the adhesion of the catalyst to the substrate and corrodes the exposed composition. This typically results in a loss of electrical efficiency (e.g., as evidenced by an increase in overpotential) and a loss of catalytic activity and a reduction in the effective life of the anode, resulting in expensive replacement. Summary of the invention

[0007] The catalytic structure obtainable by the method of the first aspect of the present invention provides a favorable balance of properties that solves these technical requirements of such anodes, while avoiding the need for large amounts of expensive precious metals, especially iridium. In particular, the catalyst-coated anode structure defined in the first aspect of the present invention exhibits high catalytic activity and selectivity for the chlorine evolution reaction, excellent durability in terms of working life and mechanical adhesion of the catalyst to the anode surface, and improved tolerance to acids formed during operation. They also have high anode conductivity, so as to maintain efficient electrical operation without excessive overpotential during long operation periods.

[0008] These advantages of the anode made by the first aspect of the invention derive from the presence of a conductive metallurgical layer of defined composition covering the electrolyte-facing surface of the anode. Such a metallurgical layer is best achieved by a method of preparation that employs the control of reactants and process conditions defined in the invention.

[0009] The present invention therefore provides in a first aspect a method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps:

[0010] a) preparing or obtaining a conductive solid substrate;

[0011] b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical composition (i) comprising providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 Compounds of ruthenium, tin and titanium in amounts;

[0012] wherein the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and

[0013] Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.

[0014] The method of the first aspect of the present invention prepares a catalytic anode structure for an electrolytic chlorine production system, which comprises a conductive solid substrate, which is covered with a conductive metallurgical layer on its surface facing the electrolyte, the layer having the morphology of aggregated particles interspersed with voids and comprising metal oxide compounds of ruthenium, tin and titanium, wherein the amount of ruthenium and tin present in the metallurgical layer provides an overall metal stoichiometric ratio of Ru:Sn of 1:≥1, based on the total content of ruthenium and tin in the metallurgical layer.

[0015] Within this specification, the term "atomic % of the total metal atomic content" with respect to a specified metal in a composition refers to the number of atoms of that metal present in the relevant composition, expressed as a percentage of the total number of atoms of the metal element present in the relevant composition, and regardless of whether such metal element is present in elemental form or in the form of a compound.

[0016] Within this specification, the term "overall metal stoichiometry" for a particular metal element refers to the stoichiometric ratio of all atoms of those metal elements present in the composite metallurgical layer (or other composition, where applicable), whether those metal elements are present in elemental form or in compound form. For example, in a structure containing 15 atomic % of ruthenium and 15 atomic % of tin in pure elemental form, the overall metal stoichiometry of Ru:Sn is 15:15 or 1:1; and in a structure containing 15 atomic % of ruthenium in the form of elemental ruthenium, 15 atomic % of elemental tin and an additional 15 atomic % of tin compounded in the form of an oxide, the overall metal stoichiometry of Ru:Sn is 15:(15+15) or 1:2.

[0017] Within this specification, the term "morphology" is used to refer to the three-dimensional structure and appearance of the material in question. Morphology can be most effectively identified by scanning electron microscopy as described below, which provides three-dimensional imaging of material surfaces in a manner that allows direct visual identification of material structure and appearance.

[0018] The present invention is based in part on the following discovery: an anode structure having excellent properties for obtaining a CER reaction in electrolytic chlorine production can be advantageously obtained by the method of the present invention, which provides a metallurgical layer on the anode surface directly exposed to the electrolyte, the layer comprising tin in combination with ruthenium and titanium. The metallurgical layer on the anode provides the anode with a surface chemical composition and a favorable morphology to achieve excellent durability in terms of working life and mechanical adhesion to the anode substrate, and provides favorable catalytic activity and selectivity for chlorine evolution reaction. The metallurgical layer also provides the anode with high acid corrosion resistance and high electrical conductivity, resulting in high electrical efficiency and long-term operation performance at low overpotential. The use of tin in the structural base composition also enables this anode performance to be achieved at a significantly lower cost than conventional catalytic anodes based on iridium and / or a larger amount of ruthenium as the main component.

[0019] In particular, the metallurgical layer composition comprises primarily a combination of ruthenium, tin and titanium in the form of metal oxides, wherein, as further demonstrated below, the presence of a minimum proportion of ruthenium in combination with titanium and the co-presence of tin in a stoichiometric amount equal to or exceeding the amount of ruthenium provide a composition capable of forming a structure having a morphology of aggregated particles interspersed with voids. Contrary to conventional thinking in the art regarding barrier layers, the particulate morphology of such a composition contributes to improved mechanical adhesion of the metallurgical layer on the substrate, such that a high adhesion layer on the electrolyte-facing surface of the anode has the above-mentioned combination of properties favorable to the chlorine evolution reaction.

[0020] Aggregated particles on the outer surface of the morphological layer are also necessary to provide highly effective and available surface area for catalytic activity. In particular, this particulate morphology overcomes the mass transfer limitations of conventional lakebed deposited catalyst layers, enabling the catalytic anodes of the present invention to operate the chlorine evolution reaction at a higher efficiency and contributing to their various advantages.

[0021] The efficiency advantage of the catalytic anode prepared by the method of the present invention in the chlorine evolution reaction is particularly demonstrated by aqueous chloride ion solutions (such as brine) with low salt content. The improved efficiency at low salt content provides an electrode with wide applicability to water treatment, for example, in addition to wastewater treatment and other chlorination applications, it is also suitable for municipal water applications or for treating drinking water. The improved efficiency also leads to lower levels of unwanted electrolysis byproducts such as chlorate and perchlorate ions.

[0022] The formation of the catalytic anode structure is accomplished by adding metallurgical layers under process conditions that are ideally conducive to forming the correct morphology of the composition.

[0023] The process of the first aspect is particularly characterized in that it uses specific starting metallurgical compositions and preparation conditions, which result in the desired anode structure.

[0024] First, comprising providing the starting composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 The use of an electrically conductive metallurgical composition (i) of compounds of ruthenium, tin and titanium in amounts of 100 wt % yields an anode metallurgical layer providing advantageous catalytic properties under the process conditions of the present invention. The defined overall metal stoichiometry of the starting composition (i) brings about in particular the desired morphology of the resulting layer, which is a layer having a morphology of aggregated particles interspersed with voids. The formation of the desired morphology is further facilitated by the use of a defined process solvent and, in some preferred embodiments, by heating the anode substrate to a temperature in the range of 50-200° C. during the application step (b).

[0025] During the application step (b), the use of a process solvent that is volatile under these conditions further enables the formation of voids in the metallurgical layer. Such a solvent also results in the concomitant loss of a certain proportion of the more volatile metal salts contained within the defined metallurgical content of the starting composition (i), so as to form a metallurgical layer having an overall metal stoichiometry with respect to ruthenium, tin and titanium that is different from the starting composition (i). The use of the defined composition (i) and the defined process conditions is believed to advantageously tolerate such concomitant loss of metal salt volatility and result in the formation of an applied metallurgical layer having the desired composition and morphology.

[0026] In a preferred embodiment, applying the metallurgical composition (i) to a substrate which is heated to a specified temperature range of 50-200°C during the application process (preferably heated to this temperature range throughout the application process) has been found to further enhance the formation of the desired metallurgical layer on the anode.

[0027] Drying the resulting structure at the same temperature range of 50-200°C has also been found to further enhance the formation of the desired metallurgical layer, and in particular to facilitate the formation of the desired morphology of a continuous layer uninterrupted by mud cracks or other significant permeability discontinuities.

[0028] It has been found that a final heat treatment of the resulting structure at a temperature of at least 450°C is essential for enhancing the formation of the desired metallurgical layer, in particular for improving the mechanical adhesion of the metallurgical layer to the anode substrate, and for facilitating a high selectivity of the chlorine evolution reaction relative to the oxygen evolution reaction from water decomposition. In this regard, a first aspect of the invention preferably is a final heat treatment in the range of 450 to 600°C, in particular an optimal final heat treatment at 500°C, where a higher selectivity for the chlorine evolution reaction and mechanical adhesion is observed.

[0029] The first aspect of the present invention also requires that the metallurgical composition is applied in step (b) using a specified process solvent, which is a mixture of isopropanol and water in a ratio range of 80:20 to 95:5 by volume, preferably in a ratio range of 82.5:17.5 to 87.5:12.5 by volume. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15. For the solubility of the starting compound used in the method of the first aspect, it has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents. In addition, it has been found that this composition of the process solvent advantageously controls the surface morphology of the layer formed by applying the metallurgical composition before and after the final heat treatment step, and is particularly conducive to the presence of aggregated particle morphology without cracks that weaken integrity. This ability to control the morphology of the layer is particularly attributed to the choice of alcohol in the process solvent and the ratio of alcohol to water, and is best controlled at a volume ratio of 85:15 (isopropanol: water).

[0030] A further aspect of the invention is also described herein and relates to an electrolytic method for catalyzing the evolution of chlorine gas from an aqueous solution containing chloride ions, which comprises passing an electric current through the solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the method of the first aspect, wherein chlorine gas is evolved from the aqueous solution at the anode.

[0031] In a preferred aspect of the electrolysis process, the chlorine gas evolved by the process is used as a biocide to disinfect water, more particularly for disinfecting ballast water or industrial wastewater, or municipal or domestic water, such as recreational water in swimming pools and domestic drinking water. In an alternative preferred aspect, the process is a chlor-alkali process for generating and recovering chlorine gas.

[0032] The present invention will now be described in more detail as follows: BRIEF DESCRIPTION OF THE DRAWINGS

[0033] This application contains the following drawings:

[0034] Figure 1 : Lake bed morphology of conventional catalyst layer with extensive “mud cracks”;

[0035] Figure 2a , Figure 2b and Figure 2c : Aggregate particle morphology of the anode surface (comparison anode and anode of the present invention), wherein Figure 2a Shown is a Ru-Sn based base layer on a titanium mesh substrate (comparative); Figure 2b Shown is a Ti-Ru-Sn based layer on a titanium mesh substrate (invention), Figure 2c Show from Figure 2b High magnification image of the base layer.

[0036] Figure 3 : Life test - Effect of the ruthenium stoichiometry in the composition (i) of the method of the invention on the durability of the metallurgical layer. DETAILED DESCRIPTION

[0037] The first aspect of the present invention (preparation method)

[0038] A first aspect provides a method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps:

[0039] a) preparing or obtaining a conductive solid substrate; and

[0040] b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical composition (i) comprising providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 Compounds of ruthenium, tin and titanium in amounts;

[0041] wherein the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropanol and water in a ratio ranging from 80:20 to 95:5 by volume; and

[0042] Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.

[0043] The process of the present invention results in a catalytic anode structure as defined below and is the preferred process for preparing such an anode.

[0044] Defined temperature conditions and process solvents in this process are important to obtain the desired catalytic anode structure.

[0045] In the method, the resulting structure is heat treated at a temperature of at least 450° C., preferably at a temperature in the range of 450 to 600° C., such as 450 to 550° C. More preferably, the resulting structure is heat treated at a temperature in the range of 475 to 525° C., most preferably at 500° C.

[0046] The method of the present invention also requires applying the metallurgical composition in step (b) using a specified process solvent, which is a mixture of isopropanol and water in a ratio range of 80:20 to 95:5 by volume, preferably in a ratio range of 82.5:17.5 to 87.5:12.5 by volume. Most preferably, the process solvent is a mixture of isopropanol and water in a volume ratio of 85:15.

[0047] With respect to the solubility of the starting compounds used in the method of the first aspect, it has been found that this composition of the process solvent exhibits advantages over similar alcoholic solvents. In addition, it has been found that this composition of the process solvent advantageously controls the surface morphology of the layer formed by applying the metallurgical composition before and after the final heat treatment step, and is particularly helpful in obtaining an aggregated particulate morphology of the resulting metallurgical layer, more preferably without integrity-weakening cracks. This ability to control the layer morphology is particularly due to the choice of alcohol in the process solvent and the ratio of alcohol to water, and is best controlled at a volume ratio of 85:15 (isopropanol:water).

[0048] Preferably, in the process of the present invention, the anodic substrate (a) is heated to a temperature in the range of 55-200°C during step (b), and the resulting structure is thereafter dried at a temperature in the same range. Preferably, the heating of the anodic substrate to this temperature range is carried out throughout step (b), and the resulting structure is thereafter dried at a temperature in the same range. Most preferably, the substrate (a) is heated to a temperature of 100°C throughout step (b), and the resulting structure is thereafter dried at this temperature.

[0049] During the application step (b) of the method, the use of a defined process solvent that is volatile under the conditions and, when present, the heat treatment of the substrate enable the formation of voids in the resulting metallurgical layer.

[0050] In particular, applying the metallurgical composition (i) to a substrate, preferably heated according to the first aspect of the invention, has been found to enhance the formation of the desired metallurgical layer on the anode. It has also been found, importantly, that drying of the resulting structure at the same temperature range enhances the formation of the desired metallurgical layer, and in particular favours the formation of a continuous layer of the desired morphology, especially a continuous layer that is not interrupted by mud cracks or other significant permeability discontinuities.

[0051] It has been found that the necessary final heat treatment of the resulting structure at a temperature of at least 450°C enhances the formation of the desired metallurgical layer, in particular, is conducive to improving the mechanical adhesion of the metallurgical layer to the anode substrate, and is conducive to a high selectivity of the chlorine evolution reaction relative to the oxygen evolution reaction from water decomposition. In this regard, the method of the present invention is preferably a final heat treatment in the range of 450 to 550°C, especially an optimal final heat treatment at 500°C, where a higher selectivity for the chlorine evolution reaction and mechanical adhesion is observed.

[0052] The temperature conditions and the use of process solvents defined above in this process, in combination with the defined metallurgical content of the starting composition (i), lead to the formation of a metallurgical layer having the desired composition and morphology on the anode substrate, which is suitable for use as a catalytic anode.

[0053] In the method of the first aspect, the composition (i) applied in step (b) comprises providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 The composition (i) is the starting composition of the metallurgical layer on the anode, and it is important in the method of the invention that the ruthenium content of the composition (i) is at a level of 0.3 or more (corresponding to 30 atomic %) stoichiometrically relative to the tin and titanium present in the composition in order to achieve the desired layer structure. It has been found that when the ruthenium in the starting composition (i) is at or above this level, the durability of the resulting composition is greatly improved when applied according to the method of the first aspect. In addition, ruthenium contributes to the overall conductivity of the composition.

[0054] In this regard, it is preferred that the composition (i) applied in step (b) of the process comprises providing the composition (i) with an overall metal stoichiometry of Ru 0.3 (Sn+Ti) 0.7 This level of ruthenium is believed to be optimal in composition (i) of the method of the present invention to produce a particularly efficient and durable anode structure.

[0055] The combined presence of tin and titanium in addition to ruthenium in the composition (i) leads, through its application in the process, to the formation of a metallurgical layer composition having the desired aggregated particle morphology and the absence of the extensive mud cracking behavior seen in other compositions comprising ruthenium and only titanium or tin. In this regard, a ruthenium content of at least 30 atomic % relative to tin and titanium in the starting composition (i) also leads under the conditions of the process to an enhanced formation of a network of aggregated particles in the morphology of the resulting composition and the absence of cracking.

[0056] The presence of tin in combination with ruthenium and titanium in composition (i) also contributes importantly to the long term durability of the anode prepared according to the method and results in improved mechanical adhesion of the metallurgical layer to the anode substrate. The tin content in composition (i) can be further adjusted so that the resulting anode has the desired overall stoichiometric ratio of Ru:Sn in the final anode structure and has the desired properties associated therewith.

[0057] To optimize these advantages, it is preferred that tin and titanium are present in composition (i) in approximately equal amounts. Thus most preferably, the composition (i) applied in step (b) comprises Ru to provide an overall metal stoichiometry of Ru to composition (i). 0.3 Sn ≥ 0.3 Ti ≤0.4 , preferably Ru 0.3 Sn 0.35 Ti 0.35 Compounds of ruthenium, tin and titanium in varying amounts.

[0058] In all of the above embodiments of the process, although minor amounts of other metal compounds may be present in addition to the essential ruthenium, tin and titanium compounds, it is preferred that composition (i) consists essentially of ruthenium, tin and titanium compounds, and more preferably, composition (i) consists of ruthenium, tin and titanium compounds, preferably in amounts that provide an overall metal stoichiometry of Ru in composition (i). 0.3 (Sn+Ti) 0.7 , most preferably providing an overall metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 .

[0059] In the method of the first aspect, an additional metallurgical composition may be applied to the surface of the metallurgical layer resulting from the application of composition (i), for example as an auxiliary catalyst composition for a specific application, as long as such auxiliary composition does not inhibit the primary effect and benefits of the layer resulting from the application of composition (i).

[0060] The composition (i) used in the process of the first aspect can be prepared from compounds known in the art for the preparation of metal oxide catalysts, which are mixed together in the presence of a process solvent in an appropriate ratio according to the teachings of the present invention. Although these compounds may include the relevant metal oxide compound where feasible, other compounds that allow better mixing or suspension and are oxidized under the subsequent heat treatment of the process to produce the desired metal oxide in situ are generally used.

[0061] Thus, it is preferred in this process that the compounds of ruthenium, tin and titanium present in composition (i) each comprise a compound other than an oxide compound; and wherein their application of heat in process step (b), followed by drying and heat treatment causes thermal decomposition of these compounds into one or more of their respective metal oxides or mixed metal oxide compounds within the composite metallurgical layer of the final anode structure.

[0062] In this regard, the compounds of ruthenium, tin and titanium present in composition (i) preferably comprise, more preferably consist of, their respective halide compounds and / or complexes with acetylacetone. These compounds provide for suitable dispersion of the metals in the composition used in the process and are subsequently converted to their respective oxides under the conditions of the process of the invention to produce the desired anode of the invention.

[0063] The starting composition (i) for the process may additionally comprise other metal compounds which bring further advantages to the resulting anode.

[0064] Thus, the starting composition (i) may additionally comprise at least one palladium compound in an amount providing a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the starting composition.

[0065] Composition (i) may additionally comprise at least one copper compound, or at least one aluminum compound or at least one nickel compound, or more than one of these, in amounts to provide composition (i) with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of the composition, or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of the composition, or a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition.

[0066] The composition (i) may additionally comprise at least one iridium compound in an amount which provides a total iridium content of at most 15 atomic %, preferably at most 10 atomic %, respectively.

[0067] These additional metal species may be introduced via compounds which are conventionally used in the art for inclusion in metallurgical coatings.

[0068] In the method of the present invention, as detailed in the first aspect of the present invention, the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.

[0069] In the process of the present invention, the metallurgical composition applied in step (b) can be applied sequentially by coating techniques known in the art, such as brushing, roller coating or knife coating, spraying (by means such as electrospraying or pressure spraying), dipping and curtain coating. Where desired, thicker coatings can be applied by multiple coating techniques on the underlying structure.

[0070] Preferably, the metallurgical composition applied in step (b) is applied sequentially by brushing one or more passes on the underlying structure, or by spraying one or more passes on the underlying structure. However, other conventional techniques may also be used to apply one or more metallurgical compositions.

[0071] The anode obtained by the method of the first aspect comprises a conductive solid substrate, on the surface facing the electrolyte of which is covered with a conductive catalytic metallurgical layer, wherein the conductive catalytic metallurgical layer has the form of aggregated particles interspersed with voids and comprises metal oxide compounds of ruthenium, tin and titanium; wherein the amount of ruthenium and tin present provides the metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥1 based on the total content of ruthenium and tin in the metallurgical layer.

[0072] These anode structures are characterized in that the outer surface of the metallurgical layer has a morphology of aggregated particles. The presence of occasional cracks or other surface discontinuities or fault lines is not excluded, wherein these defects do not expose the underlying substrate to electrolyte corrosion. However, preferably, the metallurgical layer of the anode structure has an outer surface morphology of a continuous, uncracked coating of aggregated particles interspersed with voids that increase the opportunity to reach the particle surface.

[0073] The aggregated particulate morphology of the outer surface of this metallurgical layer contrasts with the extensively cracked, deposit-like surface morphology of conventional catalytic anodes and can be best visualized by examination under scanning electron microscopy as shown in the accompanying figures. In each case, the JSM-IT500 InTouchScope TM Scanning electron microscopy instrument, Scanning electron micrographs were obtained using the settings specified in the legends to the relevant figures.

[0074] exist Figure 1 Scanning electron microscopy of the external surface morphology of a conventional catalytic anode used for electrolytic chlorine production shows a characteristic "mud crack" appearance, with extensive deep cracks radiating through a sediment-like surface coating. Such morphology renders the catalytic surface susceptible to chemical attack and weakens its structural integrity, reducing its life and usefulness.

[0075] On the contrary, Figure 2a to Figure 2c , scanning electron microscopy shows the characteristic surface of a preferred catalytic anode comprising ruthenium, tin and titanium, with uncracked aggregated particle morphology visible at the magnification shown. For further comparison, the cracking properties of a conventional ruthenium and tin (dimensionally stable anode) composition are also shown.

[0076] It is important for the anode that ruthenium and tin are present in combination with titanium in an amount that provides the metallurgical layer with an overall metal stoichiometric ratio of Ru:Sn of 1:≥1 based on the total content of ruthenium and tin in the metallurgical layer. An important discovery of the present invention is that tin is advantageously used in an overall stoichiometric amount at least equal to the amount of ruthenium, which can significantly reduce the total ruthenium content of the electrode coating, while also contributing to the advantageous combination of properties exhibited by the metallurgical layer of the present invention. In particular, the presence of tin in a defined amount contributes to the mechanical integrity of the layer and its electrical conductivity.

[0077] Based on the total content of ruthenium and tin in the metallurgical layer, the overall metal stoichiometric ratio of Ru:Sn is preferably 1:≥1.5, more preferably 1:≥2. Even more preferably, based on the total content of ruthenium and tin in the metallurgical layer, the overall metal stoichiometric ratio of Ru:Sn is 1:≥3, most preferably 1:≥5. The optimal value of this ratio in the present invention is in the range of 1:8 to 1:20, for example in the range of 1:8 to 1:15.

[0078] The individual metal contents and overall metal stoichiometry of the composite metallurgical layer may be measured by known techniques using ICP-MS (Inductively Coupled Plasma Mass Spectrometry) to determine the compositional characteristics of the present invention.

[0079] In all the above embodiments of the anode obtained from the first aspect, the metallurgical layer may further comprise an auxiliary catalyst composition distributed on the upper surface of the metallurgical layer and within the voids of the metallurgical layer. Preferably, any such auxiliary composition does not comprise a significant amount or any amount of precious metal oxides other than those provided herein, such as palladium or iridium.

[0080] Therefore, the metallurgical layer may further comprise at least one palladium compound in an amount that provides a total palladium content of up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. Preferably, a limited amount of palladium is introduced into the layer by including one or more palladium-based compounds in the composition (i) or by subsequent doping. As demonstrated by the increase in low-salt efficiency, small amounts of palladium provide further improvements in the efficiency of the chlorine evolution reaction, particularly for water treatment applications.

[0081] However, the palladium content in the composition exceeding the upper limit of 7 atomic % does not bring further improvement in the efficiency of the chlorine evolution reaction, especially for water treatment applications, as evidenced by the lack of further improvement in the low salt efficiency. Therefore, the palladium content associated with the cobalt oxide catalytic particles should be limited to a specified level to avoid unnecessary cost and complexity. Preferably, the total palladium content is at most 5 atomic %, more preferably at most 3 % of the total metal atomic content of the metallurgical layer; and optimally, the total palladium content is at most 1.5 % of the total metal atomic content of the metallurgical layer.

[0082] The anode of all embodiments from the first aspect is mainly composed of a conductive solid substrate, which is known in the art. Such a substrate is preferably basically composed of valve metals such as titanium, zirconium, niobium and tantalum (and alloys / mixtures containing these metals), preferably titanium, and most preferably basically composed of titanium. A mixture of valve metals may be present in the substrate. It can be further observed that the oxide of the valve metal substantially present in the substrate or the oxide is produced as an artificial product under the conditions of anode manufacturing and use, particularly at the substrate surface or at its interface with the composite metallurgical layer, and the substrate of the present invention does not exclude their presence, as long as they do not form the main constituent component of the substrate.

[0083] Anode substrates can be produced by conventional means in the art and can be purchased or manufactured to be customized and formed into any shape suitable for final use as an anode in an electrochemical cell or system. In particular, the substrates can be formed into meshes, plates, and more complex three-dimensional shapes such as cylinders. Depending on their design and arrangement, the substrates can be coated with a composite metallurgical layer on one or more sides.

[0084] The metallurgical layer of all embodiments of the anode obtained from the method of the first aspect comprises a metal oxide compound of ruthenium, tin and titanium, preferably consisting essentially of a metal oxide compound of ruthenium, tin and titanium, to achieve the desired stoichiometric ratio of Ru: Sn. The combination of these three metals is important for obtaining the correct morphology of the metallurgical layer composition in situ on the anode surface. Other metal oxides or other compounds may be present in addition, as long as they do not adversely affect the morphology, but most preferably, the composition consists of a metal oxide compound of ruthenium, tin and titanium.

[0085] In particular, the specific combination of ruthenium, tin and titanium provides a metallurgical layer that exhibits the desired particle morphology and is therefore also resistant to significant cracking and preferably crack-free, providing an elastic coating. In contrast, conventional coating compositions based on ruthenium and tin, for example, typically exhibit a precipitate-like "mud crack" surface (e.g., Figure 2a ) and do not provide the same resilience.

[0086] Furthermore, the specific combination of ruthenium, tin and titanium in the layer composition provides improved durability for the anode obtained from the first aspect of the invention compared to layer compositions comprising only ruthenium and titanium or only ruthenium and tin. In this respect, the combination of both tin and titanium with ruthenium provides the anode with improved anode life and improved mechanical adhesion, and further contributes to the advantages of the invention.

[0087] When the process conditions of the first aspect of the present invention are adopted, the metal stoichiometry Ru ≥0.3 (Sn+Ti) ≤0.7 The application of the starting composition (i) will achieve a suitable overall stoichiometry of these metals in the metallurgical layer, and for the method of the first aspect, it is important that ruthenium is present in the starting composition (i) at a stoichiometric level of at least 0.3 to obtain the anode and advantages of the present invention. However, within this limitation, the skilled person can vary this starting composition (i) to obtain a particularly desirable overall metal stoichiometry.

[0088] The above-described embodiments of the anode may further comprise, in addition to the above-described features, one or more additional constituent elements introduced by the method for enhancing specific properties of the anode, provided that the overall advantages of the invention are still obtained. For example, in the method of preparing the anode structure of any of the foregoing embodiments, composition (i) may further comprise a catalytic noble metal (in addition to any palladium if palladium is present), preferably iridium, in the form of its oxide or other catalytically active species, in an amount that provides a total additional noble metal content, preferably iridium content, of up to 15 atomic %, preferably up to 10 atomic %, and more preferably up to 7 atomic % of the total metal atomic content of the composite metallurgical layer. The optional presence of such small amounts of noble metal, especially iridium, may be advantageous from the perspective of further enhancing the catalytic performance of the anode, but should be limited in accordance with the purposes of the present invention to minimize the use of expensive noble metals. Therefore, such amounts of noble metal are much lower than the amounts typically used when the catalyst composition is based on such metals.

[0089] Alternatively or additionally, the anode metallurgical layer of all embodiments may further comprise at least one copper compound in an amount providing the metallurgical layer with a total metal atomic content of up to 10 atoms, preferably up to 2 atoms of the total copper content; or at least one aluminum compound in an amount providing the metallurgical layer with a total metal atomic content of up to 30 atoms, preferably up to 20 atoms of the total aluminum content; at least one nickel compound in an amount providing the metallurgical layer with a total nickel content of up to 15 atoms, preferably up to 10 atoms of the total metal atomic content; or more than one of these. The additional presence of copper, aluminum or nickel in the metallurgical layer provides further improved catalyst selectivity for the chlorine evolution reaction, as measured, for example, by low salt efficiency.

[0090] Second Aspect of the Invention (Electrolysis Method)

[0091] In a second aspect, the present invention provides an electrolytic method for catalyzing the evolution of chlorine gas from an aqueous solution containing chloride ions, which comprises passing an electric current through the solution in an electrolytic cell comprising an electrolytic anode structure obtainable by the method of the first aspect, wherein chlorine gas is evolved from the aqueous solution at the anode.

[0092] In a preferred aspect of the electrolytic process, the chlorine gas evolved by the process is used as a biocide to disinfect water, more particularly for disinfecting ballast water or industrial wastewater, or municipal or domestic water, such as recreational water in swimming pools and domestic drinking water. In an optional preferred aspect, the process is a chlor-alkali process for generating and recovering chlorine gas.

[0093] Working Example of the Invention

[0094] 1. Preparation Example

[0095] Preparation of Exemplary Starting Compositions for Use in the Methods of the Invention

[0096] 1.A Exemplary starting compositions (i) for step (b) of the process are prepared from the following component compounds and liquids available in the art:

[0097] Crystalline solid compounds:

[0098] RuCl 3. xH2O (available as a commercial product from Sigma-Aldrich),

[0099] SnCl 4. 5H2O (available as a commercial product from Sigma-Aldrich),

[0100] SbCl3 (commercially available from Sigma-Aldrich), liquid:

[0101] 2-Propanol (also known as isopropanol, available as a commercial product from Alfa Aesar),

[0102] Deionized water,

[0103] TiCl3 solution (TiCl3 is commercially available and was obtained from Sigma-Aldrich Sigma-Aldrich, dissolved in aqueous hydrochloric acid as a 12% solution).

[0104] 1.B Preparation of the starting composition (i) of the method

[0105] A metallurgical layer consisting essentially of a compound of ruthenium, tin and titanium having an overall metal stoichiometry of Ru used in the method of forming a metallurgical layer is prepared according to the following sequence: 0.3 Sn 0.35 Ti 0.35 Preferred composition (i).

[0106] To a 70 ml vial was added RuCl3.xH2O (207.6 mg; 1 mmol) and SnCl4.5H2O (409.4 mg; 1.17 mmol). These solid materials were dissolved in 2-propanol (17 ml) by vortexing until no metal precursors settled on standing. To the resulting solution was added 1.5 ml of TiCl3 solution (12% TiCl3 in hydrochloric acid, 1.17 mmol) by dropwise addition at 1,000 rpm mechanical stirring. In addition, 1.5 ml of deionized water was added dropwise to the solution. The resulting solution was aged for 5 hours at ambient conditions under 1,000 rpm mechanical stirring to produce composition (i) for use in the method of the present invention.

[0107] Preparation of catalytic anode by the method of the present invention

[0108] The method according to the first aspect of the present invention prepares the anode as follows.

[0109] A titanium mesh as an anode substrate is obtained and, after cleaning, heated to a temperature of 100°C using a hot plate. At this temperature, the composition (i) prepared above is applied to the hot substrate surface by brushing. The resulting coated sample is kept at 100°C for 1 minute, the substrate is turned over and the reverse side is coated again, and the substrate is kept at 100°C for 1 minute. The coated sample is then transferred to a 500°C oven for 5 minutes. The coated sample is then transferred back to the hot plate at 100°C and the coating and heat treatment steps are repeated. This brushing of the substrate surface with composition (i) is repeated another four times, so that a total of five brushings are applied on the surface.

[0110] Then, the dried resultant structure was finally heat treated in an oven at 500° C. for 1 hour, followed by slow cooling in the oven for 8 hours to obtain the anode structure of the present invention.

[0111] 2. Performance Examples

[0112] The following experimental techniques were used to demonstrate the performance and advantages of the anode of the present invention.

[0113] Chlorine evolution reaction (CER) life test:

[0114] The Faradaic efficiency (FE) of an electrolyser, measured regularly during long-term testing, provides important evidence of the life of the catalytic anode and, therefore, the durability of the anode for the CER reaction. A rapid increase in FE means degradation of the anode and indicates that it is approaching the end of its durability for the CER.

[0115] The electrolytic cell with counter and working electrodes was configured as described above. For experimental acceleration purposes, the working electrode (anode) was masked to 1 cm 2 To concentrate the current density. Masking was done by applying silicon tape, covered with electroplating tape. The top of the working electrode was also grounded back to the metal substrate before connection.

[0116] a) Pour 1 liter of 0.6 M NaCl solution into a beaker surrounded by a cooling jacket, which maintains the test solution at 15° C. After allowing the temperature to stabilize for 1 hour, place the electrode unit assembled above inside the beaker and connect two wires to the working electrode and the counter electrode, respectively.

[0117] b) Stir the solution at 300 rpm using a magnetic stir bar. The connected potentiostat is then set at 500 mA / cm2 under stirring conditions at 300 rpm. 2 The experiment was run in chrono-potentiometry mode until an increase of more than 12 V was recorded, at which point the result was taken as the duration of the experiment.

[0118] c) During the run, the potential of the electrolytic cell is repeatedly measured and plotted over time to report the potential for the CER over the duration of the life test and to identify the degradation point at which the potential increases rapidly and exceeds the useful life of the anode (considered as such when a voltage exceeding 12 V is recorded). 2.1 Benefits of the composition (i) of the present invention

[0119] The metallurgical layer of the anode is derived in the process of the first aspect of the invention from a composition (i) which provides an overall metal stoichiometry of Ru to the composition (i). ≥0.3 (Sn+Ti) ≤0.7 The importance of these defining features in the process of the present invention is demonstrated as follows.

[0120] Figure 3 The results of CER life tests conducted according to the above test method are reported. In each case, the working electrode (tested anode) was prepared similarly to the preparation method given in Part 1 of the Examples. Three examples of this type were prepared by varying the amount of ruthenium added to composition (i) and keeping the tin and titanium components as the balance of each composition at a 1:1 stoichiometric ratio.

[0121] like Figure 3 As shown in, the CER lifetime results indicate that when ruthenium is present at a stoichiometric level below 0.3, a long period of low overpotential (corresponding to excellent lifetime of anode catalytic performance) is not achieved. In order to avoid weakening of the layer composition and affecting the efficiency and durability of the catalytic anode for the CER reaction, the specified stoichiometry is required, wherein ruthenium is present in composition (i) at least at a stoichiometric level of 0.3.

[0122] This ruthenium stoichiometry also ensures that the desired morphology of the composition is obtained - as a layer of aggregated particles interspersed with voids. The ruthenium stoichiometry of 0.3 in composition (i) produces a structure that exhibits a well-defined crystal structure by XPS and well-defined connected particles when imaged using SEM.

[0123] like Figure 2a to Figure 2c As shown in , SEM examination after application of the metallurgical coating also revealed extensive mud cracking on the sediment-like outer surface of the anodic coating in the case of the ruthenium / tin comparative layer composition. In contrast, the coating made from the ternary base composition of the process of the present invention exhibited an uncracked coating of agglomerated particles interspersed with voids.

Claims

1. A method for preparing a catalytic anode structure for an electrolytic chlorine production system, comprising the following sequential steps: a) preparing or obtaining a conductive solid substrate ; and b) applying to the electrolyte-facing surface of the substrate a conductive metallurgical composition (i) comprising providing the composition (i) with an overall metal stoichiometry of Ru ≥0.3 (Sn+Ti) ≤0.7 Compounds of ruthenium, tin and titanium in amounts; wherein the process solvent used to apply the metallurgical composition in step (b) is a mixture of isopropyl alcohol and water in a ratio ranging from 80:20 to 95:5 by volume; and Therein, the resulting structure is subsequently dried and then heat treated at a temperature of at least 450° C.

2. A method according to claim 1, wherein during step (b) the substrate (a) is heated to a temperature in the range of 50-200°C and the resulting structure is thereafter dried at a temperature in said same range.

3. A method according to claim 1 or claim 2, wherein the substrate (a) is heated to a temperature of 100°C throughout step (b) and the resulting structure is thereafter dried at said temperature.

4. The method according to any one of claims 1 to 3, wherein after drying, the heat treatment temperature is in the range of 450 to 550°C.

5. The method according to any one of claims 1 to 4, wherein the heat treatment temperature is 500°C.

6. A method according to any one of claims 1 to 5, wherein the process solvent used for applying the metallurgical composition in step (b) is a mixture of isopropanol and water in a volume ratio of 85:

15.

7. A method according to any one of claims 1 to 6, wherein the metallurgical composition applied in step (b) is applied sequentially by brushing on the underlying structure in one or more passes.

8. A method according to any one of claims 1 to 6, wherein the metallurgical composition applied in step (b) is applied sequentially by spraying one or more passes onto the underlying structure.

9. The method according to any one of claims 1 to 8, wherein the composition (i) applied in step (b) comprises providing the composition (i) with an overall metal stoichiometry of Ru 0.3 (Sn+Ti) 0.70 Compounds of ruthenium, tin and titanium in varying amounts.

10. The method of claim 9, wherein the composition (i) applied in step (b) comprises providing the composition (i) with an overall metal stoichiometry of Ru 0.3 Sn 0.35 Ti 0.35 Compounds of ruthenium, tin and titanium in varying amounts.

11. The method according to any one of claims 1 to 10, wherein the composition (i) further comprises at least one palladium compound in an amount to provide the composition (i) with a total palladium content of preferably at most 7 atomic %, preferably at most 5 atomic %, based on the total metal atomic content of the composition (i).

12. A process according to any one of claims 1 to 11, wherein the compounds of ruthenium, tin and titanium present in composition (i) each comprise a compound other than an oxide compound; and wherein their heat treatment and, if any, their application of heat in step (b) cause these compounds to thermally decompose within the metallurgical layers of the final anode structure into one or more of their respective metal oxides or mixed metal oxide compounds.

13. The method according to claim 12, wherein the compounds of ruthenium, tin and titanium present in composition (i) comprise, preferably consist of, their respective halide or sulfate compounds and / or complexes with acetylacetone.

14. The method according to any one of claims 1 to 13, wherein the composition (i) additionally comprises at least one copper compound, or at least one aluminum compound or at least one nickel compound, or more than one of these; in amounts to provide the composition (i) with a total copper content of at most 10 atomic %, preferably at most 2 atomic %, based on the total metal atomic content of the composition (i); or a total aluminum content of at most 30 atomic %, preferably at most 20 atomic %, based on the total metal atomic content of the composition (i); or a total nickel content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition (i), respectively.

15. The process according to any one of claims 1 to 14, wherein the composition (i) additionally comprises at least one iridium compound in an amount which provides a total iridium content of at most 15 atomic %, preferably at most 10 atomic %, based on the total metal atomic content of the composition.

16. A method according to any one of claims 1 to 15, wherein the electrically conductive solid substrate consists essentially of a valve metal, preferably titanium.

17. An electrolytic method for precipitating chlorine from an aqueous solution containing chloride ions, comprising: (i) deploying the anode structure prepared according to any one of claims 1 to 16 in an electrolytic cell comprising an aqueous solution containing chloride ions; and (ii) passing an electric current through the electrolytic cell, wherein chlorine gas is evolved from the aqueous solution at the anode.

18. The electrolysis method according to claim 17, wherein chlorine evolution from the aqueous solution is promoted by the catalytic action of the metallurgical layer covering the surface of the anode.

19. An electrolysis process according to claim 17 or 18, wherein the chlorine gas evolved by the process is used as a biocide to disinfect water.

20. The electrolysis process according to claim 19, wherein the chlorine is used to disinfect ballast water, or industrial wastewater or municipal wastewater.

21. An electrolytic process according to claim 17 or 18, wherein the process is a chlor-alkali process for the generation and recovery of chlorine gas.

22. Catalytic anode obtainable by a process according to any one of claims 1 to 16.

23. Catalytic anode obtained by the process according to any one of claims 1 to 16.